Sacubitril/valsartan in heart failure and end‐stage renal insufficiency - Alex Heyse; Lynn Manhaeghe; Elien Mahieu; Céline Vanfraechem; Frederik Van Durme (ESC Heart Failure, 2019)
Abstract The aim of this report is to describe the feasibility and tolerability of medical treatment with sacubitril/valsartan in a patient treated with hemodialysis. We describe the case of a 67‐year‐old man with heart failure with reduced ejection fraction due to an ischemic cardiomyopathy and renal insufficiency undergoing hemodialysis. Because of worsening heart failure with no other therapeutic options, a treatment with sacubitril/valsartan was started. Although this patient had a very low systolic blood pressure, he could tolerate a moderate dose of 49/51 mg twice daily. After initiation of sacubitril/valsartan, there was a symptomatic improvement with a clear reduction NT‐proBNP, accompanied by a decrease in filling pressures. In conclusion, in this patient with severe heart failure undergoing hemodialysis, treatment with sacubitril/valsartan was feasible, safe, and improved heart failure symptoms.